2005
DOI: 10.1073/pnas.0505503102
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence ofClostridium botulinumtype C neurotoxin-converting phage and the molecular mechanisms of unstable lysogeny

Abstract: bacteriophage ͉ botulinum neurotoxin ͉ insertion sequence ͉ plasmid prophage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 43 publications
1
103
0
1
Order By: Relevance
“…It has been suggested to influence phage survival (Ripp and Miller, 1997), phage-dependent bacterial mortality (Ripp and Miller, 1998) and the virulence of certain bacterial strains (Sakaguchi et al, 2005). Although it has been observed that P. acnes phages can adopt pseudolysogeny (Lood and Collin, 2011), for the first time we revealed that this behavior is largely dependent on the lineages of the host strains and is not a property of the phages.…”
Section: Phage Strainsmentioning
confidence: 65%
“…It has been suggested to influence phage survival (Ripp and Miller, 1997), phage-dependent bacterial mortality (Ripp and Miller, 1998) and the virulence of certain bacterial strains (Sakaguchi et al, 2005). Although it has been observed that P. acnes phages can adopt pseudolysogeny (Lood and Collin, 2011), for the first time we revealed that this behavior is largely dependent on the lineages of the host strains and is not a property of the phages.…”
Section: Phage Strainsmentioning
confidence: 65%
“…C3bot2, an isoform of the C3 transferase with an identity of ∼65% was identified at nearly the same time (Nemoto et al 1991). Together with botulinum neurotoxin C1 or D, C3 transferase (e.g., C3bot1) from Clostridium botulinum (e.g., strain C-468) is phage-encoded (Popoff et al 1990;Sakaguchi et al 2005). A second clostridial C3-like exoenzyme was found in Clostridium limosum some years later (Just et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular and genomic analysis of the bacteriophage genome revealed that this phage exists as a circular plasmid prophage in the lysogenic state, and it does not integrate into the host chromosome. 21 The sensitivity to BoNTs seems to be widely variable among the different animal species. Cattle botulism is most frequently caused by type D or D/C toxin, followed by type C toxin, although type A, B, and C/D toxin types have also been reported.…”
Section: Bont-producing Clostridia and Their Toxinsmentioning
confidence: 99%